Figure of Mahishasuramardini - Temples of India Project Team (Jio Institute, 2024)
Mahishasuramardini, a detailed view of the presiding deity in the garbhagriha (sanctum sanctorum) of the Mahishasuramardini Temple (Temple 6), Baroli group of temples.